Chemical-induced Vitiligo - Harris, John E. (Dermatol Clin, 2017)
Chemical-induced depigmentation of the skin has been recognized for over 75 years, first as an occupational hazard but then extending to those using household commercial products as common as hair dyes. Since their discovery, these chemicals have been used therapeutically in patients with severe vitiligo to depigment their remaining skin and improve their appearance. The importance of recognizing this phenomenon was highlighted during an outbreak of vitiligo in Japan during the summer of 2013, when over 16,000 users of a new skin lightening cosmetic cream developed skin depigmentation at the site of contact with the cream and many in remote areas as well. Depigmenting chemicals appear to be analogs of the amino acid tyrosine that disrupt melanogenesis and result in autoimmunity and melanocyte destruction. Because chemical-induced depigmentation is clinically and histologically indistinguishable from non-chemically induced vitiligo, and because these chemicals appear to induce melanocyte autoimmunity, this phenomenon should be known as “chemical-induced vitiligo”, rather than less accurate terms that have been previously used.